New Religious Movements - Pathil, Kuncheria (Journal of Dharma, 1982)
Auguste Comte, the nineteenth century French social philosopher, characterized the development of human society by "the Law of the Three stages". That is, in the progress of history, mankind has passed the religious and metaphysical stages, and entered the third stage, which is scientific. According to this positivistic school of thought the modern scientific man is non-religious, secular and rationalistic. Those who support today the position of a radical secularization of man and his world would think along the same lines, that man has come of age and he can live now without the benevolence of gods, and he is thus entering into a religionless and godless world. But all the empirical evidences today seem to contradict this theory and, in fact, new religions are being born almost every day, especially in the most scientifically and technologically developed western world. Why do we have this mushroom growth of new religions today? What do these 'signs of the times' reveal to us about the needs and situations of contemporary man? What would be the fate of these new religions? Would they wither away in the hot climate of severe criticisms and attacks both from contemporary secularism and from the traditional religions?